Endovascular Treatment of Pelvic Venous Injuries - S. A. Prozorov; P. A. Ivanov; N. N. Zadneprovsky (Неотложная медицинская помощь)
Elvic vein injuries can occur with pelvic bone fractures, gunshot wound injury, iatrogenic injuries and lead to life-threatening bleeding. Ct is the main diagnostic tool in differentiating arterial from venous bleeding. Open surgical repair of venous injuries can be technically difficult. Endovascular treatment is an attractive alternative strategy. Embolization is the main method to stop arterial bleeding; balloon occlusion and stent graft implantation are also used. Arterial embolization cannot help in the situation of venous bleeding. The problem of endovascular treatment of pelvic vein injuries was not given enough attention. The purpose of this review is to summarize the available reports on the use of endovascular techniques in pelvic vein trauma and show the capabilities of the methods.